Historia, tradiciones editoriales y sociedad. Las Memorias y el Compendio de José Antonio de Plaza - Patricia Cardona (Historia Crítica, 2015)
History, in the modern sense of the word, is discourse materialized in books; diverse elements of a social, political, cultural, and economic nature have participated in the process of its configuration. This article aims to restore the historicity of History on the basis of two different types of books: the extensive ones, addressed to those with greatest reading skills, and those of a more accessible, informative nature that are directed to the majorities. In order to do so, it has turned to two books published by José Antonio de Plaza in 1850, the purpose of which was to disseminate information about the past and constitute it as a reference point of political formation of the inhabitants of the fledgling nation.